STUDI PENGARUH KONSENTRASI NaOH DAN pH TERHADAP SINTESIS SILIKA XEROGEL BERBAHAN DASAR PASIR KUARSA - Wardhani, Sri; Darjito, Darjito; Ayu, Annisa Mustikaning (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
In this research, the influence of NaOH concentration and gelation pH of the xerogel silica synthesized from quartz sand. It was extracted by NaOH 1, 2, and 3 M to obtain sodium silicate solution and was added by HCl 1M to reach pH value 7, 8, and 9 to become gel. After that it was heated at 80° C for 18 hours (aging process) to get xerogel silica. This result xerogel silica were characterized by FT-IR and XRD and its surface area was characterized by methylene blue. The optimum concentration of NaOH is 1 M with silica yield 33%. Surface area which was obtained by concentration variation of NaOH is 7 to 8 m2 / g. Surface area was not influenced by pH variation and NaOH. Characteristics using FT-IR show typical absorption of Si - O at 400 to 3000cm-1 and phase of silica xerogel by XRD is amorphous. Determination of surface area xerogel silica by methylene blue methode 7.364 m2 / g.   Key words: Xerogel, NaOH Variation, pH variation.